Want this question answered?

Be notified when an answer is posted

Add your answer:

Earn +20 pts
Q: Which is true of the infinite solutions of the inequality X0?
Write your answer...
Still have questions?
magnify glass
Related questions

What is Newton raphson's method in r programing?

It's a method used in Numerical Analysis to find increasingly more accurate solutions to the roots of an equation. x1 = x0 - f(x0)/f'(x0) where f'(x0) is the derivative of f(x0)

When x0 how many solutions is this?

x0 = 1 because any number raised to the power of 0 is always equal to 1

What is the correct procedure for epsilon-delta proofs in Calculus?

A function f(x), of a variable x, is said to have a limiting value of f(xo) as x approaches x0 if, given any value of epsilon, however small, it is possible to find a value delta such that |f(x) - f(x0)| < epsilon for all x such that |x - x0| < delta.The second inequality can be one-sided.

Equation for linear approximation?

The general equation for a linear approximation is f(x) &asymp; f(x0) + f'(x0)(x-x0) where f(x0) is the value of the function at x0 and f'(x0) is the derivative at x0. This describes a tangent line used to approximate the function. In higher order functions, the same concept can be applied. f(x,y) &asymp; f(x0,y0) + fx(x0,y0)(x-x0) + fy(x0,y0)(y-y0) where f(x0,y0) is the value of the function at (x0,y0), fx(x0,y0) is the partial derivative with respect to x at (x0,y0), and fy(x0,y0) is the partial derivative with respect to y at (x0,y0). This describes a tangent plane used to approximate a surface.

Why is 10 power 0 equal to 1?

Any number to the power zero is equal to one. That can be derived from the following index law: xa*xb = xa+b (x not zero) Now let b = 0 so that the above becomes xa*x0 = xa+0 so xa*x0 = xa (since a+0 = a) That is, any number multiplied by x0 is the number itself. That can be true only if x0 is the multiplicative identity, that is, only if x0 = 1.

Why a number to the zero power is always equal to 1?

It is a consequence of the definition of the index laws. xa * xb = xa+b If you put b = 0 in the above equation, then you get xa * x0 = xa+0 But a+0 = a so that the right hand side becomes xa Thus the equation now reads xa * x0 = xa For that to be true for all x, x0 must be the identity element for multiplication. That is x0 = 1 for all x.

The measure of the supplement of an angle exceeds twice the measure of the supplement of the complemant of the angle by 40?

The answer is -13 1/3ohere is the detailed calculation for the problem:Let x0 be the angle, then;(180 - x0) - 2[180 - (90 - x0)] =40(180 -x0) - 2[90+x0]=40180 -x0 - 180 - 2x0=40-3x0=40hencex0= -13 1/3oAny comments are welcome

what is 4E8374832E374684237eX72372+399x0+273646728-1888?

0! You said x0! anything x0=0!

Why any number raised to power zero is 1?

This derives from one of the laws of indices which states that, for any x (not = 0), xa * xb = xa+b Put b = 0 Then xa * x0 = xa+0 = xa (because a + 0 = a) But that means that x0 is the multiplicative identity. And since that is unique, and equal to 1, x0 = 1. This is true for all x. Put

Why does everything to the 0 power 1?

The multiplicative law of indices states that xa * xb = xa+b Now, if you put b = 0 in that equation you get xa * x0 = xa+0 But a+0 = a so the right hand side is simply xa Which means, the equation becomes xa * x0 = xa This is true for any x. That is, multiplying any number by x0 leaves it unchanged. By the identity property of multiplication, there is only one such number and that is 1. So x0 must be 1.

What hooks up to X0?

On a transformer connection H1 and H2 are the primary connections. X1 and X2 are the secondary connections. If your transformer has a split secondary that is grounded, that terminal is X0. The sequence is X1 - X0 - X2. The X0 usually indicates that there is a connection to a neutral wire along with the ground wire.

How can you find an equation line between two pair of points?

Assuming you want the equation of the straight line between the two points (x0, y0) and (x1, y1), the equation is: y - y0 = m(x - x0) where m is the gradient between the two points: m = (y1 - y0) &divide; (x1 - x0) Note: if the two x coordinates are equal, that is x0 = x1, then the equation of the line is x = x0.